2019
DOI: 10.1007/s00038-018-1197-0
|View full text |Cite
|
Sign up to set email alerts
|

What does ‘Keep Watch’ mean to migrant parents? Examining differences in supervision, cardiopulmonary resuscitation training and water familiarisation

Abstract: Objectives Drowning is a public health challenge. Children of migrants may be at increased risk as parents may be unaware of local water safety issues. This study explores differences between Australian-born and migrant parents in Western Australia for: (1) swimming ability; (2) supervision; (3) water familiarisation; and (4) cardiopulmonary resuscitation (CPR) training. Methods A cross-sectional survey of parents and carers of children aged under 5 years residing in WA (n = 1506) captured demographics, knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…A further 43% of children were described as not having previously had swimming or water familiarisation lessons. Given that children from culturally and linguistically diverse backgrounds accounted for 34% of incidents investigated in this study, and migrants to Australia have been identified as being less likely to have accessed water familiarisation classes for their children under five years of age [ 19 ], specific and culturally appropriate promotion of swimming lessons to migrant families is warranted. It is important also for parents and adult caregivers to also learn how to swim and know what to do in a drowning emergency.…”
Section: Discussionmentioning
confidence: 99%
“…A further 43% of children were described as not having previously had swimming or water familiarisation lessons. Given that children from culturally and linguistically diverse backgrounds accounted for 34% of incidents investigated in this study, and migrants to Australia have been identified as being less likely to have accessed water familiarisation classes for their children under five years of age [ 19 ], specific and culturally appropriate promotion of swimming lessons to migrant families is warranted. It is important also for parents and adult caregivers to also learn how to swim and know what to do in a drowning emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Although they did not satisfy the inclusion criteria, two studies reported protective factors associated with rural populations namely rural WA resident being more likely to have completed CPR training than metropolitan WA residents 50 and residents of a New South Wales rural town being less likely to make the wrong choice with respect to rip identification when compared to Australian beachgoers 51 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested multicultural communities are at a greater risk of drowning than the general Australian population due to a lack of beach safety education and swimming experience and lower participation in swim education programs [ 9 , 37 , 38 ]. It has been suggested that children of migrants are at increased risk of drowning compared to those of Australian-born parents as migrant parents are less likely to be aware of water safety issues, be able to swim and have CPR training [ 39 , 40 ]. Other barriers to swimming participation include resources, affordability and modesty [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%